2003
DOI: 10.1590/s1677-55382003000300006
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate for treatment of bone metastases in hormone refractory prostate cancer

Abstract: Introduction: Approximately 85% of patients who die from prostate cancer have bone metastases. Even though the radiological aspect of such metastases is osteoblastic, we currently know that these lesions are mixed, with coexisting blastic and lytic lesions, always beginning with bone lysis by osteoclast proliferation. Treatment options are palliative and have poor response, and when there is an improvement it is usually short-lived. This work intends to study the effect of clodronate in the treatment of skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…They might be used to treat pain related to bone metastases, 4,[8][9][10] to prevent bone osteoporosis after androgen-deprivation therapy, 5,10 to prevent skeletal events related to metastasis, 4 and even to delay or prevent metastasis formation as previously demonstrated in vitro. [11][12][13][14] The ongoing effects of bisphosphonates are being studied in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They might be used to treat pain related to bone metastases, 4,[8][9][10] to prevent bone osteoporosis after androgen-deprivation therapy, 5,10 to prevent skeletal events related to metastasis, 4 and even to delay or prevent metastasis formation as previously demonstrated in vitro. [11][12][13][14] The ongoing effects of bisphosphonates are being studied in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…8 All patients in the control group migrated to the monthly clodronate group based on evidence of the benefits of previously studied protocols. 5,8,9 Patients were strictly followed with PSA, serum testosterone (every 6 months or less), bone scintigraphy and densitometry, thoracic plain x-ray (every 6 months), and computed tomography scan, when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar placebo-controlled trial in 209 patients with hormone-refractory prostate cancer, IV clodronate administered at 1,500 mg every 3 weeks did not significantly reduce pain intensity or analgesic consumption [29]. Several uncontrolled trials of clodronate have also reported reductions from baseline pain scores [36,38,53,56,61]. Although open-label clinical trials assessing pain response must be interpreted with caution, these studies involving primarily prostate cancer patients suggest that clodronate may provide a palliative benefit [36,38,53,56,61].…”
Section: Clodronatementioning
confidence: 97%
“…Several uncontrolled trials of clodronate have also reported reductions from baseline pain scores [36,38,53,56,61]. Although open-label clinical trials assessing pain response must be interpreted with caution, these studies involving primarily prostate cancer patients suggest that clodronate may provide a palliative benefit [36,38,53,56,61]. However, in comparison with pamidronate 90 mg over a 3-month period in patients with malignant bone disease, clodronate was not as effective in reducing bone pain [42].…”
Section: Clodronatementioning
confidence: 99%
“…Ernst et al 2003;Heidenreich et al 2005;Hering et al 2003;Rodrigues et al 2004;Saad and Eastham, 2010a;Saad et al 2004;Small et al 2003]. …”
Section: Castration-resistant Prostate Cancerunclassified